Psychosocial Rehabilitation Programs Applied to Patients with Schizophrenia by Psychiatric Nurses: Systematic Review - Mahinur Betül Çalışkan; Elvan Emine Ata; Gül Dikeç (Psikiyatride Güncel Yaklaşımlar, 2021)
The purpose of this review is to review the studies related to psychosocial rehabilitation programs applied by psychiatric nurses to patients diagnosed with schizophrenia. The study was conducted on the Turkish Psychiatric Index (1) and Pubmed (7) databases between 15-31 May 2019 and 8 quantitative studies published between 2008-2019. The 27-item PRISMA Statement was used to evaluate the reporting characteristics. In this review which was written as a result of systematic screening, findings/results of 8 articles were presented as tables. In published studies, psychosocial rehabilitation programs which applied by psychiatric nurses to patients with schizophrenia; it was determined that there were trainings aimed at improving emotional expression, information technology programs including emotional recognition, psychoeducation programs after discharge, Auditory Hallucinatory symptom management program, music therapy and home visits. Also in the studies; with these psychosocial rehabilitation programs, it was determined that patients had many positive effects such as increase in social-cognitive functionality, quality of life and adherence, decrease in hospital stay and relapse, coping with Auditory Hallucinations, and improvement in emotional recognition. In the studies, it was found that there are limited number of studies conducted by psychiatric nurses in the psychosocial rehabilitation of the patient with schizophrenia and it is necessary to evaluate the results of the interventions performed by psychiatric nurses in this field.